Measuring and Evaluating the Role of ATP-Sensitive K(+) Channels in Cardiac Muscle - Kefaloyianni, Eirini (2012)
Since ion channels move electrical charge during their activity, they have traditionally been studied using electrophysiological approaches. This was sometimes combined with mathematical models, for example with the description of the ionic mechanisms underlying the initiation and propagation of action potentials in the squid giant axon by Hodgkin and Huxley. The methods for studying ion channels also have strong roots in protein chemistry (limited proteolysis, the use of antibodies, etc). The advent of the molecular cloning and the identification of genes coding for specific ion channel subunits in the late 1980’s introduced a multitude of new techniques with which to study ion channels and the field has been rapidly expanding ever since (e.g. antibody development against specific peptide sequences, mutagenesis, the use of gene targeting in animal models, determination of their protein structures) and new methods are still in development. This review focuses on techniques commonly employed to examine ion channel function in a electrophysiological laboratory. The focus is on the K(ATP) channel, but many of the techniques described are also used to study other ion channels.